Self-Esteem in Marital Relationships - Asadi Nikouyan, Matin (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The objective of this study is to explore the role of self-esteem in marital relationships, examining how self-esteem influences marital satisfaction, communication, and overall relationship dynamics.Methods: This research utilizes a descriptive analytical narrative review approach. Data were collected from valid scientific databases, including both Persian and English sources such as Google Scholar, PubMed, SID, Magiran, and IranDoc. The inclusion criteria focused on peer-reviewed studies that examined the link between self-esteem and marital relationships. A qualitative content analysis was conducted to identify key themes, patterns, and differences across the literature.Findings: The analysis reveals that self-esteem is a critical factor in marital satisfaction, with individuals possessing higher self-esteem experiencing more fulfilling and stable relationships. Self-esteem also plays a significant role in improving communication between couples, reducing marital conflicts, and enhancing emotional intimacy. Furthermore, the review highlights a reciprocal relationship between self-esteem and sexual satisfaction, where individuals with higher sexual self-esteem demonstrate better marital functioning. Cross-cultural comparisons between Persian and English literature suggest similar themes but also reveal cultural nuances in the perception and role of self-esteem within marriages.Conclusion: The findings emphasize the importance of self-esteem in marital relationships, suggesting that higher self-esteem leads to better marital satisfaction, improved communication, and reduced conflicts. Interventions aimed at boosting self-esteem, particularly among women, could have a positive impact on marital dynamics and overall family well-being. The study calls for greater attention from family counselors and institutions to promote self-esteem through workshops and educational programs, ultimately contributing to happier and more stable marriages.